Morphological control of nanostructured Ge films in high Ar-gas-pressure plasma sputtering process for Li ion batteries. (15th December 2021) - Hayashi, Junki; Nagai, Kenta; Habu, Yuma; Ikebe, Yumiko; Hiramatsu, Mineo; Narishige, Ryota; Itagaki, Naho; Shiratani, Masaharu; Setsuhara, Yuichi; Uchida, Giichiro
Abstract: We present a study on morphological control of nanostructured Ge films by the Ar gas pressure in plasma sputtering deposition. In the low Ar-gas-pressure range, aggregated islands of amorphous grains are formed on the film surface, while in the high-pressure range of 500 mTorr monodisperse nano-grains of about 30 nm in size are orderly arranged without aggregation. The film porosity shows a high value of over 10%. We tested the charge/discharge cycle performance of Li-ion batteries with nanostructured Ge films as anodes. The battery cell with an ordered arrangement structure maintained a high capacity of 434 mAh g −1 after 40 charge/discharge cycles, while that with an aggregated structure exhibited a rapid degradation of capacity to 5.08–183 mAh g −1 . An ordered arrangement of Ge nano-grains with a high porosity, which is realized in a simple one-step procedure using high Ar-gas-pressure plasma sputtering, is effective for the stable cycling of high-capacity metal anodes.